Implementação de um algoritmo dual para a otimização de sistemas decomponíveis - Lopes Filho, Dilermando Ferreira (1972)
This work deals with the optimization of decomposable systems. A decomposable mathematical programming problem is proposed ans its solution is achieved by means of dual coordination. Two basic concepts arising in large scale mathematical programming are used: outer linearization and relaxation. A cutting plane algorithm without nested constraint sets is sinthetized based on results from duality theory. Its appication to the outer linearized problem results in a convergent method for the solution of the original problem. A computer program has been developed.